A creative solution to "The problem of shelter": photographs of a university campus on an air base 1948–1969. (4th March 2021) - Kelly, Frances
ABSTRACT: Universities exert effort and expense in designing buildings to fit the current ontology and meet the perceived needs of society. This is not new – historically, entire campuses were designed to manifest pedagogical and social ideals, like the "academical village" (Coulson, Roberts and Taylor, 2015) of Thomas Jefferson's imagination. 1 Yet many campuses evolve through less deliberate means, repurposing existing sites and structures. This paper analyses one such site: a campus formed post-war when a disused air force base was adapted to house an expanding School of Engineering 1948–1969. The article takes an image-led approach, analysing a series of photographs found in an institutional archive which capture the final years of this temporary, repurposed university campus. Visual sources like these encourage reflection on material and spatial dimensions of institutional histories, enlarging our understanding of the relationship between place and knowledge, things and ideas. The images of this campus also make a case for "making do" in the university – highlighting the creative possibilities for transient sites and repurposing existing built structures.